Analysis of Service Quality on Customer Satisfaction with Servqual and Kano Model in Convenience Store XYZ Surabaya - Yasmine Azalia Wandana; Enny Aryanny (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Convenience Store XYZ Surabaya is located in the city center and commercial area, so it has high customer potential. However, this branch received a low rating of 2,5 out of 5, lower than other branches in Surabaya. Based on these problems, an improvement in service quality is carried out to customer satisfaction using the Service Quality method and the Kano Model. This study aims to determine the quality of service to customer satisfaction and provide suggestions for improvements to improve the quality of service of Convenience Store XYZ Surabaya. The results of the analysis using Service Quality show that the quality of service is 0,78, which means that the service has not met customer expectations. Through Kano Model analysis, service attributes are classified into Must Be, One Dimensional, Attractive, and Indifferent categories. The results of the analysis of the two methods show that there are 11 attributes that need to be maintained and 9 attributes that must be improved. There are several suggestions for improvements that can improve service quality at Convenience Store XYZ Surabaya such as menu innovation, employee responsiveness, employee behavior, and environmental cleanliness.